Unraveling Implicature in Racial Humor Stand-Up Comedy on YouTube - Sabila, Pasha (Universitas Lambung Mangkurat, 2023)
Humor is a form of communication with the intention to implicitly express meaning by exposing a sense of comedy. The primary focus of this thesis is to investigate implicatures in stand-up comedy, which are then categorized according to the type of humor and to observe how stereotype racial issue depicted through implicatures in stand-up comedy. This thesis examines the implicatures found in stand-up comedy with the underlying topic of racial humor on YouTube. This thesis is a qualitative research using documentation techniques and data cards as a research instrument. It utilizes Yule's implicature theory and David Hector Monro’s Theories of Humor. This thesis is limited to only 4 comedians with different backgrounds; Maz Jobrani, Hasan Minhaj, Jimmy O. Yang, and Gabriel Iglesias. The study found three categories of humor: superiority, incongruity and release. Incongruity is a major finding because it aligns with the characteristics of stand-up comedy which is to express genuinely miserable concepts while combining them with humor. This thesis discovered that the comedian's punchline indicated the existence of stereotypes regarding specific racial groups. The racial stereotype humor found is dominated by the Middle East, such as Iran, Arabia, and Indian. In addition, another finding in this thesis is the construction of Chinese identity. It can be inferred from the findings that humor belongs for particular occasions. People can use humor to express implicit meaning and to define their identity.